Rhodotorula aurantiaca penicillin V acylase: active site characterization and fluorometric studies - Kumar, Atul; Gowda, Nagaraj M.; Gaikwad, Sushama M.; Pundle, Archana (Journal of Photochemistry and Photobiology B-Biology, 2009)
Penicillin V acylase (PVA), a member of newly evolved Ntn-hydrolase superfamily, is a pharmaceutically important enzyme to produce 6-aminopenicillanic acid. Active site characterization of recently purified monomeric PVA from Rhodotorula aurantiaca (Ra-PVA), the yeast source, showed the involvement of serine and tryptophan in the enzyme activity. Modification of the protein with serine and tryptophan specific reagents such as PMSF and NBS showed partial loss of PVA activity and substrate protection. Ra-PVA was found to be a multi-tryptophan protein exhibiting one tryptophan, in native and, four in its denatured condition. Various solute quenchers and substrate were used to probe the microenvironment of the putative reactive tryptophan through fluorescence quenching. The results obtained indicate that the tryptophan residues of Ra-PVA were largely buried in hydrophobic core of the protein matrix. Quenching of the fluorescence by acrylamide was collisional. Acrylamide was the most effective quencher amongst all the used quenchers, which quenched 71.6% of the total intrinsic fluorescence of the protein, at a very less final concentration of 0.1 M. Surface tryptophan residues were found to have predominantly more electropositively charged amino acids around them, however differentially accessible for ionic quenchers. Denaturation led to shift lambda(max) from 336, in native state, to 357 nm and more exposed to the solvent, consequently increase in fluorescence quenching with all quenchers. This is an attempt towards the conformational studies of Ra-PVA. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: active site residues; Fluorometric studies; Penicillin V acylase; Rhodotorula aurantiaca